A cryptographically-linked metadata schema for academic credential interoperability: the ILMEQ model - Tasdelen, Abdulkadir; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (IEEE, 2026)
This paper presents ILMEQ (Interlinked Ledger Metadata for Educational Qualifications), a novel metadata schema that enables the representation of academic credentials as cryptographically verifiable digital assets. Aimed at addressing the shortcomings of current credentialing systems— such as lack of interoperability, vulnerability to fraud, and inadequate modeling of document relationships—ILMEQ introduces a JSON-LD-based structure that supports rich semantic linking and integrity validation. Unlike many existing blockchain-based approaches that rely on fully on-chain storage, ILMEQ maintains privacy and scalability by operating off-chain, anchoring only cryptographic hashes of credential metadata. The schema is designed to capture the full lifecycle and interdependencies of academic documents, including prerequisite chains, equivalency certifications, validation references, and revocation effects. It enables status-aware, hashverified validation of credentials without exposing sensitive content, ensuring both trust and confidentiality. ILMEQ was evaluated in three practical educational scenarios, ranging from simple undergraduate records to complex cross-border recognition cases. Results demonstrated successful modeling of linear and non-linear academic paths, effective revocation tracking, and logical propagation of status changes across related documents. The implementation includes a client-side tool for managing and exporting credential graphs, emphasizing modularity, offline capability, and user privacy. By providing a structured, machine-readable, and extensible model for academic credentials, ILMEQ significantly enhances the trustworthiness, portability, and semantic clarity of digital educational records, contributing toward a globally interoperable credentialing infrastructure.